Fandom and sport practicing: should be align but have separated - Navarro Picado, José Francisco (Estudios de Administración, 2023)
Introduction: The practice of sport is widely associated with physical and mental well-being, and at the same time sports fandom have proven to satisfy identity needs and a sense of belonging. The practice of sport should be aligned with the sport fandom, however, for some individuals, this does not seem to work that way.Objective: The main objective of this research is to understand the behavior of Costa Ricans around sports, and thus be able to identify their active lifestyle and fandom patterns.Method and technique: An exploratory study was proposed through a survey that included 403 participants. The data was collected within the Greater Metropolitan Area (GAM) under the interception methodology.Results: Only 54% of Costa Ricans say they practice sports, and 61% say they are fans of a sports club or league. However, there is a misalignment between practicing sports and fandom, where 1 in 3 Costa Ricans does one but not the other, and an additional 25% do not do either.Conclusions: The behavior of Costa Ricans regarding sports is diverse. There are individuals who practice sports intensely, and those who are very fond of it, and at the same time we have those who do not link the practicing sports with fandom. There are various aspects of pending work, both for organizations that encourage citizens to lead more active lives, and for sports organizations that require more fans committed to their favorite team.